Radiation effects on lithium metal batteries - Yuliang Gao; Fahong Qiao; Weiping Hou; Li Ma; Nan Li; Chao Shen; Ting Jin; Keyu Xie (The Innovation, 2023)
The radiation tolerance of energy storage batteries is a crucial index for universe exploration or nuclear rescue work, but there is no thorough investigation of Li metal batteries. Here, we systematically explore the energy storage behavior of Li metal batteries under gamma rays. Degradation of the performance of Li metal batteries under gamma radiation is linked to the active materials of the cathode, electrolyte, binder, and electrode interface. Specifically, gamma radiation triggers cation mixing in the cathode active material, which results in poor polarization and capacity. Ionization of solvent molecules in the electrolyte promotes decomposition of LiPF6 along with its decomposition, and molecule chain breaking and cross-linking weaken the bonding ability of the binder, causing electrode cracking and reduced active material utilization. Additionally, deterioration of the electrode interface accelerates degradation of the Li metal anode and increases cell polarization, hastening the demise of Li metal batteries even more. This work provides significant theoretical and technical evidence for development of Li batteries in radiation environments.